(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article examines the role and effectiveness of art therapy in developing children’s speech. This art-based method supports emotional stabilization, enhances communication skills, enriches vocabulary, and helps overcome psychological barriers. The study highlights that for children aged 5–6, art therapy—especially visual art activities—significantly contributes to both speech development and emotional correction. Its creative, playful, and holistic nature encourages free self-expression, imagination growth, and increased speech activity in children.